Optimized brick: print optimization - Barbosa, Ivo Vaz (2017)
This paper presents a new approach to brick prototyping that explores the capabilities of digital technologies and manufacturing techniques. The use of a clay 3D printer enables new shapes for the bricks and the definition of complex interior geometries that can adapt to its boundaries and provide a future overall performance improvement. The lack of a native software represents simultaneously a handicap and an appeal-ing opportunity to adapt the printing process to the particularities of a clay based material while maintaining full control over the final result.